The Effect of Workload and Work Environment on Employee Performance at PT. Merpati Angkasa Abadi Sultan Muhammad Kaharuddin Airport Sumbawa - Fitri Cahyaningsih; Dhiani Dyahjatmayanti (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
One of the causes of less than optimal employee performance is the ineffective division of workload and not conducive and comfortable work environment. This study aims to determine the effect of workload and work environment on employee performance at PT. Merpati Angkasa Abadi Sultan Muhammad Kaharuddin Airport, Sumbawa. This study used a quantitative research method which was conducted in September 2022 at Sultan Muhammad Kaharuddin Airport, Sumbawa. This research was conducted using sampling techniques and non-probability sampling. Data collection techniques and questionnaires. The data used is primary data obtained from filling out questionnaires by employees. The number of samples in this study were 20 employees. The research instrument was tested for validity by product moment correlation and reliability test by Cronbach Alpha. The data analysis used was multiple linear regression with the help of SPSS version 24. The results showed that the t-count for the effect of workload on employee performance was 4,216 and a sig value of 0,001. The sig value obtained 0.05 means that workload has a positive and significant effect on employee performance. Furthermore, the t-count value of the effect of the work environment on employee performance is 2.149 with a sig value of 0.046 0.05, meaning that the work environment has a positive and significant influence on employee performance. Then for the simultaneous test (F test) obtained an F-count value of 32,664 and a sig value of 0,000 or a sig value Î± (0.05). It was concluded that the performance of PT. Merpati Angkasa Abadi, Sultan Muhammad Kaharuddin, Sumbawa Airport, is affected simultaneously by workload and work environment by 79.4%. This shows that the more workload that is completed, the better the employee's performance. Likewise with the work environment, the more comfortable and conducive the work environment, the better employee performance.